English as a Foreign Language (EFL) Students’ Perception of Language Anxiety as One of the Factors Affecting Students Speaking Performance (A Phenomenological Study of Halu Oleo English Department Students - Suhardiman, Awal; Lio, Asrun; Yazid, Muhammad (Halu Oleo University, 2017)
Variety of affective variables have been confirmed to be correlated to the success in second/foreign language learning that leads to the successful language performance, one of the affective variable called language anxiety. The language anxiety is a distinct complex of self-perceptions, beliefs, feelings and behaviors related to foreign language learning due to the uniqueness of the language learning process. Thus, examining students’ perception of language anxiety in relevance with speaking performance is critical because it is only by examining their self-perception so that we can understand their positive and negative point of view that lies within the foreign language anxiety. The objective of this study are: to analyze students’ perception about language anxiety, to identify the effect of language anxiety in students speaking performances based on the students perception; to identify the sources and influential factors of the students anxiety; and to identify the solutions that may reduce students’ anxiety from the learner standpoint. Methodology that is used in this study is qualitative method especially phenomenological study. Source of data came from the students’ diary and the students’ interview result. The result of the analysis in this research, shows both from diary and interview results indicate that the English Department students of Halu Oleo University perceive English language anxiety and face high anxiety-provoking situations in their speaking performances that negatively affects their academic life. The main sources of students’ anxiety are speak in public, afraid of making mistakes, unfriendly lecturer, afraid of negative evaluation, inability to express, fear of failure, incomprehensible input, inability to comprehend, remembering target rules and grammar, poor pronunciation, lack of vocabulary and poor knowledge of English language. In conclusion, regarding the solution both students and teachers need to deal with anxiety-provoking situations carefully and execute the solutions of reducing anxiety